Malignant phyllodes tumours show stromal overexpression of c-myc and c-kit. - Sawyer, E; Poulsom, R; Hunt, F; Jeffery, R; Elia, G; Ellis, I; Ellis, P; Tomlinson, I; Hanby, A (2003)
Phyllodes tumours are fibroepithelial neoplasms of the breast, the stroma of which can undergo malignant progression to sarcoma. The frequency of malignant lesions varies in different series from 5% to 30%. The aim of this study was to elucidate potential molecular mechanisms in the progression to malignancy in phyllodes tumours. c-myc and c-kit were studied at the protein, RNA(c-myc only) and DNA level. We chose to study c-myc as we have previously shown that Wnt signalling is important in benign, but not malignant, phyllodes tumours. If c-myc is constitutively activated in malignant tumours, this may provide an explanation for why the Wnt pathway is no longer important in these tumours. c-kit is a membrane-bound tyrosine kinase receptor and overexpression is characteristic of gastrointestinal stromal tumours. A previous report suggested that this may also be the case in malignant phyllodes tumours, and we wished to confirm this. We assessed expression of c-myc and c-kit in 30 phyllodes tumours (10 malignant) using in situ hybridization (c-myc) and immunohistochemistry (c-myc and c-kit). 9/10 malignant tumours showed c-myc expression in the stroma, compared to 7/20 benign tumours (p = 0.006, Fisher's exact test). Stromal c-kit expression was found in 5/10 malignant tumours, compared to 1/20 benign tumours (p = 0.008, Fisher's exact test). One tumour had high-level amplification of c-myc, but we found no evidence of mutations of c-kit. We hypothesize that the overexpression of c-myc may drive stromal proliferation in malignant phyllodes tumours, and that c-kit overexpression contributes to the growth of these lesions. c-kit may also be a new therapeutic target in these tumours.